Analisis Transmisi Harga Cabai Merah Keriting (Capsicum annuum L.) di Provinsi Kepulauan Bangka Belitung - Wikrawardana, Sucy; Agustina, Fournita; Evahelda, Evahelda (Universitas Galuh, 2025)
ABSTRACT Curly red chili (Capsicum annum L.) is a horticultural commodity whose production, availability and price affect inflation and the national economy including in Bangka Belitung. Fluctuations in the price of curly red chili often vary depending on the amount of availability and the number of needs for curly red chili in the community. The price dynamics that occur in the market between marketing institutions for curly red chili commodities in the Bangka Belitung Islands Province are quite interesting to study. This study aims to analyze the transmission of curly red chili prices starting from producers, wholesalers to consumers. The research method is secondary time series data for 5 years (2019-2023) with Asymmetric Error Correction Model (AECM) analysis. The results of the study show that the transmission of curly red chili prices between institutions in the Bangka Belitung Islands Province runs symmetrically. This study shows the importance of efficient marketing distribution chains and price stability policies in order to maintain the stability of curly red chili prices in Bangka Belitung